PERAN MODERASI KOMPETENSI KOMITE AUDIT PADA HUBUNGAN ANTARA STRUKTUR KEPEMILIKAN DAN KUALITAS PELAPORAN KEUANGAN - Erik Gautama; Fransiskus E. Daromes; Suwandi Ng (Universitas Katolik Indonesia Atma Jaya, 2017)
This research is aimed to investigate the influence of the competence of audit committee on the relationship between the corporate ownership structure and reporting quality. We used secondary data, which is the annual report of listed companies at Indonesia Stock Exchange from 2013-2016 respectively. The sampling method is purposive sampling where the researcher obtained 116 companies as the sample. Data examination uses multiple linear regression analysis using IBM SPSS program (Statistical Program for Social Science) 20 in data processing. The results showed that family ownership, and foreign ownership has a positive but not significant effect on the financial reporting quality, while family ownership and audit committee competence has a positive and significant effect on financial reporting quality, as well as foreign ownership and audit committee competence has a positive and significant effect on the financial reporting quality. The result of this research is expected to be a consideration and recommendation for the firms to fill audit committees with people who have competence / expertise in accounting and finance and improve the ownership structure so that the monitoring function becomes effective and efficient in achieving the objectives of the conceptual framework of financial reporting which leads to reducing the manipulation of financial statements.